Latihan Fisik Meningkatkan Kadar Insulin-Like Growth Factor-1 (IGF-1) - Wibawa, Junian Cahyanto; Mus, Rosdiana; Gama, Noviyanty Indjar; Rivarti, Arina Windri (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2021)
This article aims to determine the effect of physical activity in increasing insulin-like growth factor 1 (IGF-1 levels. The method used is a systematic literature review with public databases, direct science, national and international journals with vulnerabilities in 2015-2020. The results showed that physical activity could increase IGF-1 levels. IGF-1 levels are closely related to muscle building, muscle mass, and muscle strength. IGF 1 levels that occur during physical activity can reduce sarcopenia, muscle weakness, and obesity. Given theimportant role physical activity plays in increasing IGF-1 levels, this article looks at how physical activity affects the increase in IGF-1 levels. It can be concluded that physical activity can increase IGF-1 levels as one of the factors associated with increased muscle mass.